Exploring the Reasons Behind Divorce in Muslim Families - Ediz, M Hidayat; Datres, Datres; Yusrial, Yusrial; Zulfadli, Zulfadli; Biswadi, Biswadi; AN, Rusydi; M, Gusmarni (Samara: Journal of Islamic Law and Family Studies, 2024)
Divorce among Muslim families has become a growing phenomenon over the past few decades. Despite Islam's emphasis on the importance of family and marriage, many Muslim couples face difficulties in maintaining their marriages. This study aims to understand the reasons behind divorce among Muslim families. This qualitative study employed a phenomenological approach, with data collected through in-depth interviews with ten informants selected using purposive sampling. All informants were Muslim couples who had experienced divorce. In addition to in-depth interviews, the researcher also conducted document analysis from the Ministry of Religion of the Republic of Indonesia from 2016 to 2024. All data were analyzed using thematic analysis techniques by Miles and Huberman. The study's findings indicate that the reasons behind divorce among Muslim families are complex and multifaceted. However, the most common reasons include continuous conflicts and quarrels, poor communication, domestic violence, differences in values and beliefs, economic pressure, and lack of knowledge on building a harmonious family. This study contributes to a deeper understanding of the reasons behind divorce among Muslim families. The findings can also be used as a reference for developing more effective programs and services to prevent and address divorce among Muslim families